Pergamon, Türkei: Die Arbeiten des Jahres 2014 - Pirson, Felix (e-Forschungsberichte des DAI, 2023)
The activities of the Pergamon-excavation in 2014 were part of the continuing research program on the urban organism of the Hellenistic residential city and on Pergamon´s countryside. The program also includes studies of the ancient necropolis and the natural sanctuaries as integral elements within the presentation of suburbs and hinterland. The campaign focused on (1) the inner-city survey at the western slope of the city-hill and the western periphery, (2) the excavation of the alleged rock-cut sanctuaries 4 and 2, (3) the excavation within the alleged banquet-building at the northern eastslope, (4) the excavation of the south-eastern necropolis, (5) the archaeological and architectural study of the Lower Agora, (6) the geophysical prospection of large scale gravemounds in the periphery of the ancient city and finally (7) the new Kane-Pensinsula (Kara Dağ) regional harbor survey. The extensive conservation and restoration works have already been presented in a separate report. A detailed preliminary report will be published in “Archäologischer Anzeiger” 2015/2.